2021
DOI: 10.3389/fmicb.2021.640066
|View full text |Cite
|
Sign up to set email alerts
|

CARD-FISH in the Sequencing Era: Opening a New Universe of Protistan Ecology

Abstract: Phagotrophic protists are key players in aquatic food webs. Although sequencing-based studies have revealed their enormous diversity, ecological information on in situ abundance, feeding modes, grazing preferences, and growth rates of specific lineages can be reliably obtained only using microscopy-based molecular methods, such as Catalyzed Reporter Deposition-Fluorescence in situ Hybridization (CARD-FISH). CARD-FISH is commonly applied to study prokaryotes, but less so to microbial eukaryotes. Application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 247 publications
(449 reference statements)
3
63
0
Order By: Relevance
“…Recent studies conducted mostly in freshwater systems have been dealing with characterizing the growth rates of major bacterivorous taxa (Grujcic et al ., 2018 ; Šimek et al ., 2018 , 2020 ). So, for a better understanding of the bacterial grazing and its impact on microbial food web structure, it is still necessary to investigate the physiological parameters of the dominant marine HF taxa (Piwosz et al ., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies conducted mostly in freshwater systems have been dealing with characterizing the growth rates of major bacterivorous taxa (Grujcic et al ., 2018 ; Šimek et al ., 2018 , 2020 ). So, for a better understanding of the bacterial grazing and its impact on microbial food web structure, it is still necessary to investigate the physiological parameters of the dominant marine HF taxa (Piwosz et al ., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another method that can directly enumerate specific taxa is fluorescence in situ hybridization (FISH), which recruits a fluorescently labeled probe that can hybridize the complementary sequences in the targeted cells. Because of its high sensitivity, it has been used to detect and/or quantify low abundance microbes and those with “low ribosome content” [ 66 , 67 ]. Although FISH provides only a relative abundance measurement, it can be combined with flow cytometry and microscopy to determine the absolute abundance of each taxon of interest independently of all bacterial members [ 63 , 68 , 69 ].…”
Section: Decision-making Regarding Different Biological Questionsmentioning
confidence: 99%
“…Kuo et al, 2021 designed four different probes using dyes Cy3, FAM, Texas red, and Cy5, respectively, and successfully detected four coliform bacteria ( E. coli , K. pneumoniae , E. aerogenes , and C. freundii ) in water samples [ 70 ]. Detecting rare taxa in a community using FISH requires a great number (500–1000) of counted cells to maximize the precision of the targeted count [ 67 ].…”
Section: Decision-making Regarding Different Biological Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to study protists from a variety of biomes have unearthed a vast diversity and begun to map their distributions at a global scale (22)(23)(24). Such investigations have brought insights into protist environmental preferences and community assembly processes (25)(26)(27)(28), food web dynamics (29)(30)(31)(32)(33), symbioses (34)(35)(36), viruses (37), functional traits (38), and bioindicator values (39,40). Large-scale lake surveys have shown that protist assemblages are shaped by broad biogeographic patterns (41)(42)(43) but are also influenced by local environmental factors and interactions with bacteria (44).…”
Section: Introductionmentioning
confidence: 99%